Anode for fluoride ion secondary battery and fluoride ion secondary battery including the same
By using zirconium fluoride and metal zirconium in the negative electrode, the battery capacity and coulombic efficiency of fluoride ion secondary batteries are enhanced, addressing the limitations of conventional aluminum fluoride-based batteries.
Patent Information
- Application Number
- JP2021010554
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-01-26
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2041-01-26
AI Technical Summary
Conventional fluoride ion secondary batteries face challenges with low battery capacity due to the insulating properties of aluminum fluoride, which hinders electrochemical reactions, and the lack of ionic conductivity in lithium-doped aluminum fluoride limits the concentration of the negative electrode active material.
Incorporating zirconium fluoride with an average particle diameter of 100 nm or less as the negative electrode active material, along with metal zirconium, a solid electrolyte made of fluoride ion conductive fluoride, and a conductive additive, enhances ionic conductivity and allows for higher concentrations without increasing volume, thereby increasing battery capacity and improving coulombic efficiency.
The use of zirconium fluoride and metal zirconium in the negative electrode results in a fluoride ion secondary battery with increased battery capacity, improved coulombic efficiency, and enhanced charging and discharging reversibility.
Smart Images

Figure 0007616890000001 
Figure 0007616890000002 
Figure 0007616890000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a negative electrode for a fluoride ion secondary battery and a fluoride ion secondary battery including the same. [Background technology]
[0002] Conventionally, fluoride ion secondary batteries using fluoride ions as a carrier have been proposed (for example, see Patent Documents 1 to 6). Fluoride ion secondary batteries are expected to have battery characteristics that exceed those of lithium ion secondary batteries, and various studies have been conducted in recent years.
[0003] For example, aluminum-based materials are candidates for the negative electrode active material of fluoride ion secondary batteries. Among them, the use of aluminum fluoride has been studied, but aluminum fluoride has an issue in that it is difficult for electrochemical reactions to occur because it has electrical insulation properties. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2019-87403 A [Patent Document 2] JP 2017-50113 A [Patent Document 3] JP 2019-29206 A [Patent Document 4] JP 2018-206755 A [Patent Document 5] JP 2018-198130 A [Patent Document 6] JP 2018-92863 A Summary of the Invention [Problem to be solved by the invention]
[0005] Therefore, the applicant has realized a fluoride ion secondary battery using a negative electrode active material made of aluminum fluoride doped with lithium metal, but the current situation is that further improvement of the battery characteristics is required. In particular, the negative electrode active material made of aluminum fluoride doped with lithium metal does not have good ion conductivity, so the concentration of the negative electrode active material in the negative electrode cannot be increased, and it is not easy to increase the battery capacity.
[0006] The present invention has been made in view of the above, and has an object to provide a fluoride ion secondary battery having a larger battery capacity than conventional batteries. [Means for solving the problem]
[0007] (1) The present invention provides a negative electrode for a fluoride ion secondary battery, comprising a negative electrode active material, the negative electrode active material comprising zirconium fluoride.
[0008] (2) In the negative electrode for a fluoride ion secondary battery of (1), the zirconium fluoride may have an average particle size of 100 nm or less.
[0009] (3) In the negative electrode for a fluoride ion secondary battery according to (1) or (2), the content of the zirconium fluoride in the negative electrode for a fluoride ion secondary battery may be less than 50 mass %.
[0010] (4) In the negative electrode for a fluoride ion secondary battery of any one of (1) to (3), the negative electrode active material may further contain metallic zirconium.
[0011] (5) In the negative electrode for a fluoride ion secondary battery of (4), the average particle size of the zirconium metal may be 75 μm or less.
[0012] (6) In the negative electrode for a fluoride ion secondary battery according to (4) or (5), the content of the metallic zirconium in the negative electrode for a fluoride ion secondary battery may be 8 mass % or less.
[0013] (7) The present invention also provides a fluoride ion secondary battery comprising a negative electrode for a fluoride ion secondary battery according to any one of (1) to (6). Effect of the Invention
[0014] According to the present invention, it is possible to provide a fluoride ion secondary battery having a larger battery capacity than conventional batteries. [Brief description of the drawings]
[0015] [Figure 1] FIG. 1 is a diagram showing the characteristics of aluminum fluoride and zirconium fluoride. [Diagram 2] 1A to 1C are diagrams illustrating an example of a method for producing a negative electrode for a fluoride ion secondary battery according to an embodiment of the present invention. [Diagram 3] 5A to 5C are diagrams illustrating another example of the method for producing the negative electrode for a fluoride ion secondary battery according to the embodiment. [Figure 4] 1 is an electron microscope photograph of zirconium fluoride composed of microparticles before being subjected to ball mill grinding treatment. [Diagram 5] 1 is an electron microscope photograph of zirconium fluoride composed of microparticles after ball milling treatment. [Figure 6] Electron microscope image of nanoparticles of zirconium fluoride after ball milling. [Figure 7] FIG. 13 is a diagram showing charge / discharge curves of negative electrode half-cells for fluoride ion secondary batteries according to Example 4 and Comparative Example 1. [Figure 8] FIG. 2 is a diagram showing charge / discharge curves of negative electrode half-cells for fluoride ion secondary batteries according to Example 1 and Comparative Example 2. [Figure 9] FIG. 2 is a diagram showing charge / discharge curves of negative electrode half-cells for a fluoride ion secondary battery according to Examples 1 to 3. [Figure 10] FIG. 2 is a graph showing the relationship between the zirconium fluoride concentration and the capacity in the negative electrode half-cells for fluoride ion secondary batteries according to Examples 1 and 4 to 6. [Figure 11]FIG. 1 is a diagram showing charge / discharge curves of negative electrode half cells for fluoride ion secondary batteries according to Examples 1 and 8. [Figure 12] FIG. 2 is a graph showing the relationship between the metallic zirconium concentration and the capacity and Coulombic efficiency in the negative electrode half-cells for fluoride ion secondary batteries according to Examples 1 and 8 to 10. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, an embodiment of the present invention will be described in detail with reference to the drawings.
[0017] [Negative electrodes for fluoride ion secondary batteries] The negative electrode for a fluoride ion secondary battery according to this embodiment contains zirconium fluoride as a negative electrode active material. A negative electrode for a fluoride ion secondary battery containing zirconium fluoride has not been found so far, and the negative electrode for a fluoride ion secondary battery according to this embodiment is characterized in that it contains zirconium fluoride.
[0018] Zirconium fluoride functions as a negative electrode active material during charging and discharging. Specifically, zirconium fluoride converts fluoride ions F - During discharge, fluoride ions F - As the zirconium fluoride, a commercially available product can be used.
[0019] The average particle size of the zirconium fluoride according to this embodiment is preferably 100 nm or less, that is, the zirconium fluoride is preferably composed of nanoparticles having an average particle size of 100 nm or less. By using the zirconium fluoride composed of nanoparticles having an average particle size of 100 nm or less as the negative electrode active material, the battery capacity can be increased. The more preferable average particle size of the zirconium fluoride is 65 nm or less.
[0020] The content of zirconium fluoride in the negative electrode for a fluoride ion secondary battery according to this embodiment is preferably less than 50% by mass. The higher the zirconium fluoride concentration in the negative electrode for a fluoride ion secondary battery, the higher the charge capacity. However, when the zirconium fluoride concentration in the negative electrode for a fluoride ion secondary battery reaches 50% by mass, the resistance in the negative electrode increases and the voltage drops, causing a rapid drop in charge capacity and making it difficult to charge and discharge. The content of zirconium fluoride is more preferably 40% by mass or less.
[0021] Here, Fig. 1 is a diagram showing the characteristics of aluminum fluoride and zirconium fluoride. Fig. 1 shows the literature values (theoretical values) and actual measured values of the density of aluminum fluoride AlF3 that has been conventionally studied and zirconium fluoride ZrF4 according to this embodiment, and also shows the ionic conductivity of both at 140°C, which is assumed to be during operation of a fluoride ion secondary battery.
[0022] As shown in Figure 1, zirconium fluoride can be made denser than conventional aluminum fluoride, and has a high ionic conductivity. Therefore, zirconium fluoride can have a higher concentration than aluminum fluoride, and the battery capacity can be increased. In addition, since zirconium fluoride can suppress an increase in volume even if its concentration is increased, it is possible to increase the content of the solid electrolyte made of fluoride ion-conductive fluoride and the content of the conductive additive, which will be described later, and as a result, a higher ionic conductivity can be obtained.
[0023] The negative electrode active material according to the present embodiment preferably further contains metallic zirconium. By using a negative electrode active material containing metallic zirconium, the coulombic efficiency, which is the ratio of the discharge capacity to the charge capacity, can be improved, and the reversibility of charge and discharge can be improved. As the metallic zirconium, a commercially available product can be used.
[0024] In particular, the negative electrode for a fluoride ion secondary battery according to this embodiment preferably contains a solid electrolyte made of a fluoride ion conductive fluoride, which will be described later. However, if a reaction occurs due to the solid electrolyte, the discharge capacity cannot be obtained sufficiently with respect to the charge capacity. In contrast, in this embodiment, by containing metallic zirconium, the reaction due to the solid electrolyte can be suppressed, and a high discharge capacity can be obtained, thereby improving the reversibility of charge and discharge. In addition, since the charge capacity can be used for discharge with little loss, the fluoride ion secondary battery according to this embodiment is expected to have a long life.
[0025] The average particle size of the metallic zirconium is preferably 75 μm or less. That is, the metallic zirconium is preferably composed of particles having an average particle size of 75 μm or less. By including metallic zirconium composed of particles having an average particle size of 75 μm or less, the battery capacity can be increased while improving the reversibility of charging and discharging.
[0026] The content of metallic zirconium in the negative electrode for a fluoride ion secondary battery according to this embodiment is preferably 8% by mass or less. As the concentration of metallic zirconium in the negative electrode for a fluoride ion secondary battery increases, the coulombic efficiency increases, but the amount of electrolyte decreases, the resistance in the negative electrode increases, and the voltage drops, resulting in a decrease in the charge capacity. However, if the content of metallic zirconium in the negative electrode for a fluoride ion secondary battery is 8% by mass or less, the decrease in the charge capacity can be suppressed. A more preferred content of metallic zirconium is 5% by mass or less.
[0027] The negative electrode for a fluoride ion secondary battery according to this embodiment preferably further contains a solid electrolyte made of a fluoride ion conductive fluoride and a conductive assistant, in addition to zirconium fluoride or metallic zirconium as the above-mentioned negative electrode active material.
[0028] The fluoride ion conductive fluoride is not particularly limited as long as it has fluoride ion conductivity. For example, CeBaF x and BaLaF yExamples of fluoride ion conductive fluorides include Ce. 0.95 Ba 0.05 F 2.95 YaBa 0.6 La 0.4 F 2.4 By including these fluoride ion conductive fluorides in the negative electrode for a fluoride ion secondary battery according to this embodiment, the fluoride ion conductivity can be improved.
[0029] The average particle size of the fluoride ion conductive fluoride is preferably in the range of 0.1 μm to 100 μm. If the average particle size of the fluoride ion conductive fluoride is within this range, a thin-layer electrode can be formed while having relatively high ion conductivity. The average particle size of the fluoride ion conductive fluoride is more preferably in the range of 0.1 μm to 10 μm.
[0030] The conductive assistant may be any one having electronic conductivity and is not particularly limited. For example, carbon black or the like is used as the conductive assistant. As the carbon black, furnace black, ketjen black, acetylene black, or the like can be used. By including these conductive assistants in the negative electrode for a fluoride ion secondary battery according to this embodiment, the electronic conductivity can be improved.
[0031] The average particle size of the conductive assistant is preferably in the range of 20 nm to 50 nm. If the average particle size of the conductive assistant is within this range, an electrode having high electronic conductivity can be formed with a small weight.
[0032] Moreover, the negative electrode of the fluoride ion secondary battery according to this embodiment may contain other components such as a binder, within a range that does not impair the effects of this embodiment.
[0033] Next, a method for producing a negative electrode for a fluoride ion secondary battery according to this embodiment will be described in detail with reference to FIGS. Here, Fig. 2 is a diagram showing an example of a method for producing a negative electrode for a fluoride ion secondary battery according to the present embodiment, and Fig. 3 is a diagram showing another example of a method for producing a negative electrode for a fluoride ion secondary battery according to the present embodiment.
[0034] In one example of the manufacturing method shown in FIG. 2, first, CeBaF as a solid electrolyte made of a fluoride ion conductive fluoride is prepared. x (Ce 0.95 Ba 0.05 F 2.95 ) and 50 mg of carbon black (acetylene black AB) as a conductive additive are mixed.
[0035] Next, 250 mg of zirconium fluoride ZrF4 is added to the mixture, and then, for example, 400 rpm, 15 minutes, 40 cycles of ball milling are performed. This results in the composite ZrFCB of the negative electrode for the fluoride ion secondary battery according to the present embodiment. Then, the composite ZrFCB obtained is pressed together with a negative electrode current collector such as gold foil at a predetermined pressure to be integrated, thereby producing the negative electrode for the fluoride ion secondary battery according to the present embodiment.
[0036] The mixing ratio of zirconium fluoride and the fluoride ion conductive fluoride can be selected arbitrarily. However, as described above, the content of zirconium fluoride in the negative electrode for a fluoride ion secondary battery is preferably less than 50 mass%, and from the viewpoint of increasing the charging capacity, the ratio of the fluoride ion conductive fluoride, which is the fluorine source, is preferably high.
[0037] In addition, the average particle size of the zirconium fluoride to be added is preferably selected appropriately so that it becomes nanoparticles having an average particle size of 100 nm or less after ball mill pulverization. For example, when adding zirconium fluoride composed of microparticles having an average particle size of 100 μm, the zirconium fluoride can be pulverized by ball mill pulverization.
[0038] Fig. 4 is an electron microscope photograph of zirconium fluoride composed of microparticles before ball milling. Fig. 5 is an electron microscope photograph of zirconium fluoride composed of microparticles after ball milling. As shown in Figs. 4 and 5, zirconium fluoride composed of microparticles can be pulverized by the ball milling to a particle size of at least about 300 nm, but the average particle size remains microparticles.
[0039] In contrast, Figure 6 is an electron microscope photograph of zirconium fluoride composed of nanoparticles after ball milling. As shown in Figure 6, when zirconium fluoride with an average particle size of 65 nm or 20 nm shown in Figure 2 is added, there is almost no change in the average particle size after ball milling. In other words, the particle size of zirconium fluoride with an average particle size of 65 nm or 20 nm is maintained as it is.
[0040] Returning to FIG. 3, in another example of the manufacturing method shown in FIG. 3, similarly to the example shown in FIG. 2, first, CeBaF as a solid electrolyte made of a fluoride ion conductive fluoride is prepared. x (Ce 0.95 Ba 0.05 F 2.95 ) and 50 mg of carbon black (acetylene black AB) as a conductive additive are mixed.
[0041] Next, 250 mg of zirconium fluoride ZrF4 with an average particle size of 20 nm, and 50 mg of metal zirconium Zr with an average particle size of 2 μm are added to the mixture, and then, for example, 400 rpm, 15 minutes, and 40 cycles of ball mill pulverization are performed. This results in the composite ZrFCB of the negative electrode for the fluoride ion secondary battery according to this embodiment. Then, the obtained composite ZrFCB is pressed together with a negative electrode current collector such as gold foil at a predetermined pressure to be integrated, thereby producing the negative electrode for the fluoride ion secondary battery according to this embodiment.
[0042] According to the negative electrode for a fluoride ion secondary battery according to the present embodiment described above, the following effects are achieved.
[0043] In the negative electrode for a fluoride ion secondary battery according to this embodiment, zirconium fluoride is included as the negative electrode active material. As described above, zirconium fluoride can be made denser than conventional aluminum fluoride, and has high ionic conductivity. Therefore, zirconium fluoride can have a higher concentration than conventional aluminum fluoride, and therefore the battery capacity can be increased. In addition, since zirconium fluoride can suppress an increase in volume even if its concentration is increased, the content of the solid electrolyte made of fluoride ion conductive fluoride and the content of the conductive assistant can be increased, resulting in a higher ionic conductivity.
[0044] As described above, the present applicant has realized a fluoride ion secondary battery using a negative electrode active material obtained by doping lithium metal into aluminum fluoride, but there is a demand for further improvement in battery characteristics. In particular, the negative electrode active material obtained by doping lithium metal into aluminum fluoride does not have good ion conductivity, so the concentration of the negative electrode active material in the negative electrode cannot be increased. Therefore, the capacity density of the battery (battery capacity per mass) cannot be increased, and the Coulomb efficiency of the first charge / discharge cycle is low at about 50%. Therefore, the negative electrode for a fluoride ion secondary battery according to this embodiment is configured to further contain metallic zirconium in addition to zirconium fluoride as the negative electrode active material. As a result, by using a negative electrode active material containing metallic zirconium, the Coulomb efficiency, which is the ratio of discharge capacity to charge capacity, can be dramatically improved, and the reversibility of charge / discharge can be dramatically improved.
[0045] [Fluoride ion secondary battery] The fluoride ion secondary battery according to this embodiment includes the above-mentioned negative electrode for fluoride ion secondary batteries. The fluoride ion secondary battery according to this embodiment also includes a solid electrolyte layer made of a solid electrolyte having fluoride ion conductivity, and a positive electrode.
[0046] As the solid electrolyte constituting the solid electrolyte layer, a conventionally known solid electrolyte can be used. Specifically, the same fluoride ion-conducting fluoride as described above can be used.
[0047] As the positive electrode, a conventionally known positive electrode active material is used, and it is preferable to use a positive electrode that can obtain a sufficiently high standard electrode potential compared to the standard electrode potential of the negative electrode for the fluoride ion secondary battery according to this embodiment. In addition, by selecting a material that does not have fluoride ions as the positive electrode, a battery that can be started by charging can be realized. In other words, it becomes possible to manufacture a battery in a discharge state where the energy state is low, and the stability of the active material in the electrode can be improved.
[0048] Specific examples of the positive electrode material include Pb, Cu, Sn, Bi, Ag, etc., conductive additives, binders, etc. For example, a positive electrode can be manufactured by pressing a positive electrode mixture containing lead fluoride, tin fluoride, carbon black, etc. together with a positive electrode material and a lead foil or the like as a current collector at a predetermined pressure to integrate them.
[0049] Therefore, the fluoride ion secondary battery according to the present embodiment can be manufactured by sequentially stacking the negative electrode for the fluoride ion secondary battery according to the present embodiment, the solid electrolyte layer, and the positive electrode. The fluoride ion secondary battery according to the present embodiment exhibits the same effects as the negative electrode for the fluoride ion secondary battery according to the present embodiment.
[0050] The present invention is not limited to the above-described embodiment, and the present invention includes modifications and improvements within the scope that can achieve the object of the present invention. For example, in the above embodiment, the present invention is described as being applied to a solid-state battery, but is not limited thereto, and may be applied to a fluoride ion secondary battery that uses an electrolytic solution instead of a solid electrolyte layer. EXAMPLES
[0051] Next, examples of the present invention will be described, but the present invention is not limited to these examples.
[0052] [Examples 1 to 3] Negative electrode composite powders for fluoride ion secondary batteries according to Examples 1 to 3 were produced according to the manufacturing method for the negative electrode for fluoride ion secondary batteries according to this embodiment shown in Fig. 2. Zirconium fluoride having an average particle diameter of 65 nm was used in Example 1, zirconium fluoride having an average particle diameter of 20 nm was used in Example 2, and zirconium fluoride having an average particle diameter of 2 µm was used in Example 3. In addition, the content of zirconium fluoride in the negative electrode for fluoride ion secondary batteries in all of Examples 1 to 3 was set to 25 mass%.
[0053] [Examples 4 to 7] According to the manufacturing method of the negative electrode for a fluoride ion secondary battery according to the present embodiment shown in Fig. 2, negative electrode composite powders for a fluoride ion secondary battery according to Examples 4 to 7 were produced. Zirconium fluoride having an average particle size of 65 nm was used in all of Examples 4 to 7. The content of zirconium fluoride in the negative electrode for a fluoride ion secondary battery was 12.5 mass% in Example 4, 30 mass% in Example 5, 40 mass% in Example 6, and 50 mass% in Example 7.
[0054] [Examples 8 to 10] According to the manufacturing method of the negative electrode for a fluoride ion secondary battery according to the present embodiment shown in Fig. 3, negative electrodes for a fluoride ion secondary battery according to Examples 8 to 10 were produced. Metal zirconium having an average particle size of 2 µm was used in all of Examples 8 to 10. The content of metal zirconium in the negative electrode for a fluoride ion secondary battery was 8 mass% in Example 8, 1 mass% in Example 9, and 5 mass% in Example 10.
[0055] [Comparative Examples 1 and 2] A modified AlF3 negative electrode active material obtained by doping lithium metal on aluminum fluoride, which has already been proposed by the applicant in PCT / JP2019 / 039886 as a conventional negative electrode for a fluoride ion secondary battery, was produced as a negative electrode for a fluoride ion secondary battery according to Comparative Examples 1 and 2, according to the manufacturing method described in PCT / JP2019 / 039886. In both Comparative Examples 1 and 2, modified AlF3 having an average particle size on the order of nanometers was used, and the content of modified AlF3 in the negative electrode for a fluoride ion secondary battery was 12.5% by mass in Comparative Example 1, and 25% by mass in Comparative Example 2.
[0056] [Charge / discharge test] A half cell was prepared using the negative electrode for a fluoride ion secondary battery prepared in each Example, and a constant current charge / discharge test was carried out. Specifically, a potentiogalvanostat device (Sotron, SI1287 / 1255B) was used to carry out a constant current charge / discharge test under a vacuum environment of 140°C, with a charge current of 0.04 mA and a discharge current of 0.02 mA, a lower limit voltage of -2.2 V, and an upper limit voltage of -0.1 V.
[0057] Each half-cell was prepared by pressing at a pressure of 40 MPa using a tablet press to produce a cylindrical pellet-type cell. Specifically, each half-cell was prepared by feeding, in a tablet press, gold foil (99.99%, thickness 10 μm) manufactured by Nilaco Corporation as a negative electrode current collector, 10 mg of the negative electrode composite powder for fluoride ion secondary batteries prepared in each Example, 200 mg of solid electrolyte, 30 mg of positive electrode composite powder, and gold foil (99.99%, thickness 20 μm) manufactured by Nilaco Corporation as a positive electrode material and positive electrode current collector in this order.
[0058] [Results / Discussion] Fig. 7 is a diagram showing charge / discharge curves of negative electrode half cells for fluoride ion secondary batteries according to Example 4 and Comparative Example 1. As shown in Fig. 7, when comparing Example 4 using zirconium fluoride ZrF4 and Comparative Example 1 using modified AlF3, both of which have a negative electrode active material concentration of 12.5 mass%, it was confirmed that Example 4 has a larger ratio of discharge capacity to charge capacity (Coulomb efficiency) and improved reversibility of charge / discharge.
[0059] Fig. 8 is a diagram showing charge / discharge curves of the negative electrode half-cells for fluoride ion secondary batteries according to Example 1 and Comparative Example 2. As shown in Fig. 8, comparing Example 1 using zirconium fluoride ZrF4 and Comparative Example 2 using modified AlF3, both of which have a negative electrode active material concentration of 25 mass%, it was confirmed that while Comparative Example 2 had almost no capacity, Example 1 had a large capacity and the utilization rate was 100%.
[0060] FIG. 9 is a diagram showing charge and discharge curves of the negative electrode half cells for fluoride ion secondary batteries according to Examples 1 to 3. Here, the capacity actually obtained is expressed as the utilization rate with respect to the theoretical capacity. The theoretical capacity of zirconium fluoride is 1.6 mAh at a concentration of 25 mass %, and as shown in FIG. 9, the capacity of the microparticles of Example 3 having an average particle diameter of 100 μm (the particle diameter after ball milling is smaller) was about 1.1 mAh. In contrast, the capacity of the nanoparticles of Example 1 having an average particle diameter of 65 nm and the nanoparticles of Example 2 having an average particle diameter of 20 nm was both about 1.6 mAh. From this result, it was confirmed that the utilization rate of nanoparticles is higher than that of microparticles.
[0061] Fig. 10 is a diagram showing the relationship between the zirconium fluoride concentration and the capacity in the negative electrode half cells for fluoride ion secondary batteries according to Examples 1 and 4 to 7. As shown in Fig. 10, the higher the zirconium fluoride concentration in the negative electrode for fluoride ion secondary batteries, the higher the charge capacity, and when the zirconium fluoride concentration in the negative electrode for fluoride ion secondary batteries reaches 50 mass%, the resistance in the negative electrode increases and the voltage drops, causing a rapid drop in charge capacity and making it difficult to charge and discharge. From this result, it was confirmed that the preferred concentration of zirconium fluoride in the negative electrode for fluoride ion secondary batteries is less than 50 mass%, and more preferably 40 mass% or less.
[0062] Fig. 11 is a diagram showing charge / discharge curves of the negative electrode half cells for a fluoride ion secondary battery according to Examples 1 and 8. As shown in Fig. 11, it was confirmed that, compared to Example 1 in which zirconium fluoride was used as the negative electrode active material, Example 8 in which 8 mass % of metallic zirconium was added to the entire negative electrode for a fluoride ion secondary battery was used as the negative electrode active material, the discharge capacity was increased and the reversibility of charge / discharge was improved.
[0063] FIG. 12 is a diagram showing the relationship between the metal zirconium concentration and the capacity and the Coulombic efficiency in the negative electrode half cells for fluoride ion secondary batteries according to Examples 1 and 8 to 10. As shown in FIG. 12, it was found that the higher the metal zirconium concentration in the negative electrode for fluoride ion secondary batteries, the higher the Coulombic efficiency becomes from about 80% or more to nearly 100%, while the charging capacity gradually decreases. This is because, when the metal zirconium concentration increases, the amount of electrolyte decreases, the resistance in the negative electrode increases, and the voltage decreases. Therefore, it was confirmed from this result that if the metal zirconium concentration in the negative electrode for fluoride ion secondary batteries is 8 mass% or less, the Coulombic efficiency can be improved while suppressing the decrease in charging capacity.
Claims
1. A negative electrode for a fluoride ion secondary battery comprising a negative electrode active material, The negative electrode active material contains zirconium fluoride, The negative electrode for a fluoride ion secondary battery, wherein the zirconium fluoride has an average particle size of 100 nm or less.
2. A negative electrode for a fluoride ion secondary battery comprising a negative electrode active material, The negative electrode active material contains zirconium fluoride, A content of the zirconium fluoride in the negative electrode for a fluoride ion secondary battery is less than 50 mass %.
3. A negative electrode for a fluoride ion secondary battery comprising a negative electrode active material, The negative electrode for a fluoride ion secondary battery, wherein the negative electrode active material contains zirconium fluoride and metallic zirconium.
4. 4. The negative electrode for a fluoride ion secondary battery according to claim 3, wherein the average particle size of the metallic zirconium is 75 μm or less.
5. 5. The negative electrode for a fluoride ion secondary battery according to claim 3, wherein the content of said metallic zirconium in said negative electrode for a fluoride ion secondary battery is 8 mass % or less.
6. A fluoride ion secondary battery comprising the negative electrode for a fluoride ion secondary battery according to claim 1 .
Citation Information
Patent Citations
Fluoride ion conductor and electrochemical element using the same
JP1992238815A
Metal fluoride compositions for self-assembling batteries
JP2013510409A
Fluoride ion battery
JP2017050113A
Fluoride ion all solid state battery
JP2018092863A
Fluoride ion battery
JP2018198130A